Three act tragedy - Christie, Agatha, 1890-1976. (New York : Berkley Books, 1984)
When two people are murdered at different dinner parties with the same guest list, Hercule Poirot decides to have a dinner party of his own.
Young Adult
Keywords: Murder -- Fiction; Poirot, Hercule (Fictitious character); Homicide -- Fiction; Mystery fiction; Parties -- Fiction; Poirot, Hercule (Fictional character); Detective and mystery stories